Polyphenol-rich extract of roselle improves oxidative stress status, renal function and structure of diabetic rat - Fatima Mohammed Yusr,; Fatin Farhana Jubaidi,; Sumayyah Ismail,; Siti Balkis Budin, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Diabetic nephropathy is a progressive chronic renal disease, that leads to renal failure mediated by oxidative stress. Roselle or Hibiscus sabdariffa is well-known for its health benefits and is rich in polyphenols with high antioxidant activities. Limited studies evaluate the effects of polyphenol-rich extract of roselle (HPE) on the development of diabetic nephropathy. Hence, this study aimed to determine the effect of HPE in the renal of diabetic rats focusing on oxidative stress, renal function, and structural changes. Type 1 diabetes mellitus was induced in adult male Sprague-Dawley rats which were then divided into three groups: untreated diabetes (DM), HPE-supplemented diabetic rats (DM+HPE), and metformin-treated diabetic rats (DM+MET). Non-diabetic rats (NDM) served as normal controls. All rats were left untreated for four weeks followed by another four weeks of treatment, respectively. At the end of the study, all rats were sacrificed whereby blood was collected for creatinine level analysis, and kidneys were collected for oxidative stress and antioxidant markers as well as histological analyses. Data showed that HPE reduced blood glucose and creatinine levels significantly and improved catalase (CAT) activity. HPE supplementation also reduced the lipid and protein oxidation process, marked by significant reductions in malondialdehyde (MDA) and advanced oxidation protein products (AOPP). Moreover, HPE supplementation improved renal structure, especially in reducing glomerulus degeneration and renal tubule damage. In conclusion, this study suggests that HPE is able to reduce renal damage by mitigating oxidative stress and improving antioxidant status that potentially prevents the progression of diabetic nephropathy in diabetic rat model.